2023
DOI: 10.3390/su151310531
|View full text |Cite
|
Sign up to set email alerts
|

Selected Motivations of Student Sports Volunteers in Terms of Professional Activity and Previous Volunteering Experience

Abstract: Involvement in sports volunteering is not only a way to improve mental health by increasing a sense of appreciation or respect, but it also allows participants to take on an individual challenge, meet new people, or gain specific knowledge. The aim of this study was to analyze selected motivations of students from the University of Physical Education in Krakow to get involved in sports volunteering during the 2023 European Games organized in their city and verifying them in terms of gender, age, previous volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Studies related to this aspect have been carried out both during mega sporting events, such as the Summer and Winter Olympic Games, as well as during local events. Many volunteers want to participate in sporting events because of their well-being, good mental health, and the opportunity to increase their self-confidence and integrate with others with like-minded interests [58][59][60]. Studies have also shown that the motivation to participate in sporting events depends on the type of event and the form in which it is organized.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…Studies related to this aspect have been carried out both during mega sporting events, such as the Summer and Winter Olympic Games, as well as during local events. Many volunteers want to participate in sporting events because of their well-being, good mental health, and the opportunity to increase their self-confidence and integrate with others with like-minded interests [58][59][60]. Studies have also shown that the motivation to participate in sporting events depends on the type of event and the form in which it is organized.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%